Solar Photocatalytic Degradation of Food Dye (Tartrazine) using Zinc Oxide Catalyst - Nasri Abdul Rahman, Muhammad; Aireen Abd Rahim, Nor; Farahiyah Wan Kamarudin, Wan; Irwan, Zildawarni; Rahman Mat Amin, Abd; Muhammud, Adida; Munirah Muda, Siti; Erni Fazlina Mohd. Akhir, Noor (International Journal of Engineering and Technology, 2018)
Food dyes are used in food processing industries as coloring and additive so that the food can be stored for a long time. The effluent discharged from the industries has become a serious issue as it can cause water pollution. Solar photocatalytic degradation was widely used to degrade most of the dyes in wastewater due to its high effectiveness. The main objective of this study was to investigate the effectiveness of degradation of Tartrazine using the photocatalytic process by using ZnO as photocatalyst and sunlight as the irradiation source. This study also was conducted to compare the percentage degradation of Tartrazine at different conditions which are amount of catalyst, pH of dye solution, exposure time and presence and absence of sunlight and photocatalyst. The degradation of Tartrazine was analyzed by using UV-Vis spectrophotometer. A laboratory set-up was designed to evaluate the optimum weight of ZnO, optimum pH of Tartrazine solutions, optimum time exposure and also was operated in the presence of ZnO as photocatalyst and sunlight as the irradiation source. The result showed that, the photocatalytic degradation of Tartrazine proved to be effective under solar radiation by using ZnO as photocatalyst. The optimum photodegradation occurred at optimum weight of ZnO, pH of Tartrazine and time of radiation. The optimum weight of ZnO was 20 mg, and the optimum pH of Tartrazine solution was pH 6. The most effective condition for photodegradation of Tartrazine was degradation with ZnO catalyst and with solar radiation. The radiation time was 1 hour with (93.91Â±0.57) % degradation. The formation of OHâˆ™ required both the presence of catalyst and solar radiation.Â Â